Educators, professional bodies and the future of the valuation profession. Issue 4 (20th August 2018) - Wilkinson, Sara; Halvitigala, Dulani; Antoniades, Hera
Abstract : Purpose: Valuers face significant challenges as valuation becomes automated and the role evolves from economic analysis to data handling and processing. The purpose of this paper is to identify new knowledge and skills Valuers will need in the future and the role of professional bodies and educators in meeting future challenges in Australia, although the issues are considered global. Design/methodology/approach: This qualitative research sought a deeper understanding of the issues, threats, challenges, opportunities, new areas of practice and knowledge that Valuers were experiencing with a view to identifying the role of professional bodies, industry and educators to meet the challenges. A focus group approach was adopted to collect data from practitioners in Sydney and Melbourne. Findings: The roles of the professional body the Australian Property Institute, industry/employers and educators to meet these future challenges were identified. Changes are required to degree programme content in respect of digital technologies and statistical knowledge and skills. Continuing professional development programmes are required to address knowledge and skills gaps in existing practitioners. Research limitations/implications: In this study, key limitations were that focus group participants were from Melbourne and Sydney only, and the focus is NSW and Victoria centric, although many participants have international work experience. Overall there was under representation of rural Valuers, of small valuation firms, of young, recently joined or qualified Valuers and females. Originality/value: This is original research and highlights some real threats, issues and challenges facing the Australian Valuers. It complements work undertaken by legal and accounting professional bodies who perceive change and uncertainty affecting membership and services. To address and where, appropriate, embrace the changes that are coming and those already here, a manifesto for action for educators and the professional body is established.